THE ORIGINS OF THE RISK INVESTMENT PROJECTS REAL IMPACTED BY INFLATION - E. Bogomolova; S. Dzarasuev; D. Belousova (Вестник университета)
In the article analyses the origins of inflation in Russian modern terms, moreover it focuses on impact of inflation process on risk appearance by realization of investment projects in the real sections of economy.